Varicose veins - Collares, Felipe B.; Faintuch, Salomão (Practical guides in interventional radiology., 2017)
Chronic venous disease is a common condition, with a prevalence as high as 50% in industrialized countries worldwide. Of those, about 20-25% of women and 10-15% of men have visible varicose veins. Varicose vein treatment has become an increasingly multidisciplinary field, and one that has seen cutting-edge advances and significant growth. Felipe B. Collares, Salomao Faintuch, and a team of venous disease experts have compiled, Varicose Veins, a concise book that covers the full range of interventional procedures for venous insufficiency. Following introductory chapters on anatomy and pathophys